2014
DOI: 10.1093/hmg/ddu392
|View full text |Cite
|
Sign up to set email alerts
|

Functional variations modulating PRKCA expression and alternative splicing predispose to multiple sclerosis

Abstract: The protein kinase C alpha (PRKCA) gene, encoding a Th17-cell-selective kinase, was repeatedly associated with multiple sclerosis (MS), but the underlying pathogenic mechanism remains unknown. We replicated the association in Italians (409 cases, 723 controls), identifying a protective signal in the PRKCA promoter (P = 0.033), and a risk haplotype in intron 3 (P = 7.7 × 10(-4); meta-analysis with previously published data: P = 4.01 × 10(-8)). Expression experiments demonstrated that the protective signal is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…Conversely, a significant dysregulation of GSDMB AS profile was evident in RR-MS cases, whose levels of exon 6 and exons 5–8 skippings were unrelated to the rs11078928 polymorphism. This same dysregulation of AS profiles in MS cases, characterized by the loss of genotype-dependent splicing in the presence of a polymorphism directly affecting a splice site, has been already described for at least two other genes ( PRKCA and NFAT5 ) [11,12], thus possibly representing a specific “signature” of the disease status. The loss of genotype-dependent regulatory mechanisms might be explained by the extensive general dysregulation of proteins involved in the splicing process observed by us and other groups in MS [12,35,36,37].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Conversely, a significant dysregulation of GSDMB AS profile was evident in RR-MS cases, whose levels of exon 6 and exons 5–8 skippings were unrelated to the rs11078928 polymorphism. This same dysregulation of AS profiles in MS cases, characterized by the loss of genotype-dependent splicing in the presence of a polymorphism directly affecting a splice site, has been already described for at least two other genes ( PRKCA and NFAT5 ) [11,12], thus possibly representing a specific “signature” of the disease status. The loss of genotype-dependent regulatory mechanisms might be explained by the extensive general dysregulation of proteins involved in the splicing process observed by us and other groups in MS [12,35,36,37].…”
Section: Discussionsupporting
confidence: 67%
“…After 8 h of treatment, total RNA was extracted and GSDMB expression levels were evaluated by semi-quantitative real-time RT–PCRs, using primers anchored to the 3′ terminus region of the transcript, common to all splicing variants (Figure 2). Two different transcripts of the PRKCA gene (respectively sensitive and insensitive to NMD) were used as positive and negative controls of the treatment [11]. We observed a significant increase of the total level of GSDMB after cycloheximide treatment in both cell lines with respect to the untreated sample (HEK293: 2.64-fold, p = 0.0019; HepG2: 2.8-fold, p = 0.00090) (Figure 2), suggesting that, in physiologic conditions, GSDMB mRNA levels are downregulated by NMD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are conflicting reports about whether a C/T transition SNP (rs912428) in LRCH1 is a risk factor for human osteoarthritis (Snelling et al, 2007; Jiang et al, 2008). Considering that SNP polymorphisms of PKCα have been identified in MS patients, and PKCα-deficient mice are resistant to EAE (Barton et al, 2004; Meisel et al, 2013; Paraboschi et al, 2014), this makes us even more interesting to further investigate whether SNP polymorphisms in DOCK8 or LRCH1 are associated with MS using a large population of MS samples.…”
Section: Discussionmentioning
confidence: 99%
“…For both mutations, computer-assisted splice-site prediction analysis recognized a significant difference between the wild-type and the mutant sequences, suggesting that they might impact SLC45A2 splicing. These predictions were tested by a well-validated in vitro hybrid minigene approach, 26,29,30 which we have recently applied to the study of two novel splicing mutations in the OCA2 gene. 31 Functional analysis demonstrated that both mutations inactivate the relevant physiologic donor splice site and, at the same time, may lead to the activation of cryptic sites.…”
Section: Discussionmentioning
confidence: 99%